2020
DOI: 10.21451/1984-3143-ar2019-0111
|View full text |Cite
|
Sign up to set email alerts
|

Current and alternative trends in antibacterial agents used in mammalian semen technology

Abstract: How to cite: Santos CS, Silva AR. Current and alternative trends in antibacterial agents used in mammalian semen technology. AbstractThe use of antibacterial substances as additives in extenders for ensuring the sanitary quality of the semen employed in reproductive biotechniques and preserving it from bacterial deterioration has been reported since the mid-twentieth century. However, the deleterious effects of these drugs on the sperm quality as well as their effectiveness in controlling bacterial growth in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 59 publications
1
16
0
1
Order By: Relevance
“…However, Althouse et al (2000) described in their study that most of the bacteria isolated in the inseminating doses were resistant to gentamycin. According to Scheid (2000) and Santos and Silva (2020), it is essential to maintain a strict hygienic standard and to add antibiotics to the semen diluents. Gentamycin, penicillin, streptomycin, neomycin and lincomycin are the most commonly used antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Althouse et al (2000) described in their study that most of the bacteria isolated in the inseminating doses were resistant to gentamycin. According to Scheid (2000) and Santos and Silva (2020), it is essential to maintain a strict hygienic standard and to add antibiotics to the semen diluents. Gentamycin, penicillin, streptomycin, neomycin and lincomycin are the most commonly used antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…Contamination can occur as a result of the infection of male reproductive tract, but also through semen collection and processing to obtain seminal doses (Úbeda et al 2013;Kuster and Althouse 2016;Santos and Silva 2020). In boar semen, bacteria belonging to at least 25 different genera have been detected as contaminants, with the most frequently occurring ones being Escherichia, Pseudomonas, Staphylococcus and Proteus (Althouse and Lu 2005).…”
Section: Introductionmentioning
confidence: 99%
“…10 Antibacterial agents against the antibiotic resistance strains have been discovered. 11,12 Conventional phage therapy has shown hopeful results in human clinical cases. 13,14 In animal models and in vitro studies, phages are used as therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…These authors concluded that the presence of gentamicin could affect sperm function during cooled storage [67] Llincomycin and spectinomycin Sperm DNA fragmentation index was greater in the samples containing these antibiotics than in those without. Sperm motility, membrane integrity and mitochondrial membrane potential were not different between semen samples with and without lincomycin and spectinomycin [64] Potassium penicillin G-amikacin disulfate, ticarcillin disodium-potassium clavulanate, piperacillin sodium/tazobactam sodium, or meropenem Slight differences were detected for sperm motility and kinematics and in chromatin integrity when various antibiotic combinations were used [68] Adding amikacin sulfate and potassium penicillin G to INRA-96 ® extender (already contains penicillin, gentamicin and amphoteracin-B)…”
Section: Referencementioning
confidence: 99%
“…An extensive range of antimicrobial substances is used in semen extenders for various species [ 64 ]. These latter authors summarized the antibiotics used for stallion sperm samples, including amikacin, cefquinome, ceftiofur, clavulanic acid, gentamicin, meropenem, penicillin, and ticarcillin.…”
Section: Bacteria In Semenmentioning
confidence: 99%